Pośrednik ubezpieczeniowy w Niemczech. Wybrane zagadnienia. Część II - Przybytniowski, Jarosław W. (Przegląd Prawno-Ekonomiczny, 2009)
Streszczenie dostępne wyłącznie w języku angielskim: The fundamental change of German law is liquidation of previous unlimited freedom of performing insurance intermediary job, according to which there were no limits in access to this job (everyone could be an insurance intermediary). According to new regulations, insurance agency as business activity requires permission (§ 34d GewO). The regulation follows existing duty for permission in real estate commerce loans and investment (§ 34c GewO). Insurance agents need to fulfill many formal and legal requirements in domain of qualifications, guarantee of proper service, legal liability to gain permission and registry. While insurance servicing, intermediaries must inform advice and evidence given advices. Not untieing the above-mentioned may bring sanctions.